2022
DOI: 10.3390/land11112043
|View full text |Cite
|
Sign up to set email alerts
|

Historical Changes in Urban and Peri-Urban Forests: Evidence from the Galați Area, Romania

Abstract: In Romania, urban and peri-urban forests (UPUF) have been subject to significant transformations during the past centuries, especially during the post-communist period. The current paper seeks to provide an integrated assessment of UPUF in one of the most dynamic and densely populated urban areas in Romania, i.e., Galați, in terms of historical overview, forest structure and dynamics, and conservation of forest ecosystems, and the way all these aspects are reflected in the toponymy. The analysis covers three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Despite the traditional focus on wood production, there is a growing interest in quantifying the carbon sequestration capacity of Romanian forests, which are characterised by a wide range of climatic, vegetative and soil conditions due to their extensive altitudinal gradient [33]. Besides, studies on peri-urban forests in Romania quantifying the carbon stock and carbon stock change over time are very scarce, instead focusing on forest structure and diversity [34,35] or historical changes in the forest-covered areas [36]. Additionally, according to the National Forest Inventory [33], around half a million hectares of forest are outside of the national forest area, and peri-urban forests are partially one of them, with significant implications on the national greenhouse gasses inventory report regarding carbon sequestration by different pools [37].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the traditional focus on wood production, there is a growing interest in quantifying the carbon sequestration capacity of Romanian forests, which are characterised by a wide range of climatic, vegetative and soil conditions due to their extensive altitudinal gradient [33]. Besides, studies on peri-urban forests in Romania quantifying the carbon stock and carbon stock change over time are very scarce, instead focusing on forest structure and diversity [34,35] or historical changes in the forest-covered areas [36]. Additionally, according to the National Forest Inventory [33], around half a million hectares of forest are outside of the national forest area, and peri-urban forests are partially one of them, with significant implications on the national greenhouse gasses inventory report regarding carbon sequestration by different pools [37].…”
Section: Introductionmentioning
confidence: 99%
“…All over the world, there is a migration of people to urban agglomerations [19,20]. Previous studies have shown that urbanization is often associated with changes in the layout of urban green spaces [21,22]. Urbanization increases the sealing of existing catchments, which results in, among other things, changes in the dynamics and volume of surface runoff and a reduction in the intensity of groundwater recharge [23][24][25].…”
Section: Introductionmentioning
confidence: 99%